A Factor Analysis of the Fetzer/Nia Brief Multidimensional Measure of Religiousness/Spirituality (MMRS) - Piedmont, Ralph L. (Research in the social scientific study of religion, 2006)
The Brief Multidimensional Measure of religiousness/Spirituality (Fetzer Institute/NIA Working Group, 1999) was developed to capture in abbreviated form an array of spiritual/religious constructs that were related to psychosocial and health outcomes. Little research has examined the psychometric aspects of this hybrid scale. Using 452 undergraduate students, normative information at both the item and scale level was provided. The factor structure of the instrument and correlations with personality and family environment were obtained. Results indicated that several of the scales lack reliability, and the issue of how well these scales reflect their original, longer parents remains in question. Principal components analyses indicated that the items of the MMRS constitute three dimensions that are mostly independent of personality. Spirituality and religiosity emerged as highly correlated, unidimensional constructs.